2020
DOI: 10.1177/1042258719899423
|View full text |Cite
|
Sign up to set email alerts
|

When Can Families Fill Voids? Firms’ Reliance on Formal and Informal Institutions in R&D Decisions

Abstract: Firms are more prone to allocate their resources to research and development (R&D) when they are confident about their ability to appropriate the value created through these activities. In this regard, policymakers introduce formal intellectual property rights (IPR) institutions to create an innovation-friendly environment. Less formalized shared values and norms are however likely to affect the extent to which organizations depend on the strength of formal institutions in determining their R&D strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 121 publications
(168 reference statements)
1
32
3
Order By: Relevance
“…Second, whereas the prior studies have demonstrated that the institutional environment matters for the strategies (Brinkerink & Rondi, 2020) and financial performance of family firms (Banalieva et al, 2015; Liu et al, 2010), we demonstrate which national institutions boost family firm growth, showing that firms grow faster in countries with more democracy, government effectiveness, regulatory quality, rule of law, corruption control, and political stability. We also document how the positive moderating effect of the institutional environment varies across different types of family firms and different business cycles.…”
Section: Discussioncontrasting
confidence: 75%
“…Second, whereas the prior studies have demonstrated that the institutional environment matters for the strategies (Brinkerink & Rondi, 2020) and financial performance of family firms (Banalieva et al, 2015; Liu et al, 2010), we demonstrate which national institutions boost family firm growth, showing that firms grow faster in countries with more democracy, government effectiveness, regulatory quality, rule of law, corruption control, and political stability. We also document how the positive moderating effect of the institutional environment varies across different types of family firms and different business cycles.…”
Section: Discussioncontrasting
confidence: 75%
“…Second, we consider how proactive orientation can weaken family firm preferences for patenting, relative to secrecy, as a means of value protection and capture. Previous literature has analysed the effect of family involvement, an informal institution, on the relationship between the strength of formal IP rights institutions in a country and the firm's R&D resource allocation decisions (Brinkerink and Rondi, 2020). However, R&D decisions are related to family firm inputs into the innovation process, and not the mechanism they select to protect and capture the IP once it has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, such a preference may be influenced by whether SMEs are family owned-or-controlled (Howorth et al, 2010). Contemporary work has examined how family involvement, as an informal mechanisms or institution, moderates the relationship between the strength of formal IP in a country and the R&D resource allocation decisions by such firms (Brinkerink and Rondi, 2020). However, R&D decisions are related to SME inputs to the innovation process, and not the mechanism they select to protect the IP once it has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…These loyal and strong relationships include those between family owners and firm employees (Karra et al, 2006; Sirmon & Hitt, 2003) as well as external stakeholders, such as business partners and government officials (Aldrich & Cliff, 2003; Ge et al, 2019; Soleimanof et al, 2018). Considering the institutional environment, family firms then utilize these strong relationships to overcome institutional weaknesses (Brinkerink & Rondi, 2020; Khanna & Palepu, 2000; Luo & Chung, 2013; Miller et al, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…On the one hand, family firms are perceived as anchors of economic stability (Anderson & Reeb, 2003a; Astrachan & Shanker, 2003) and are thought to benefit from high institutional quality compared to nonfamily firms (Botero et al, 2015; Carney et al, 2011; La Porta et al, 1999; Wang & Shailer, 2017). On the other hand, family firms have advantages when dealing with weak institutions (Brinkerink & Rondi, 2020; Gilson, 2007; Khanna & Palepu, 2000; Miller et al, 2009) and may be able to exploit these institutional weaknesses through their political connections (Dinh & Calabrò, 2019; Fisman, 2001; Morck & Yeung, 2004; Peng, 2003). Research has found both positive and negative effects of family involvement in emerging markets, given that such markets are generally characterized by institutional weakness (Claessens et al, 2002; Dau et al, 2020; Khanna & Rivkin, 2001; Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%